Mark Manders : Night drawings from Self-portrait as a building. - Greene Naftali Gallery, New York (Arnhem : ROMA, 2000)
Newspaper with drawings with all the titels on the frontpage.
Mark Manders : Reduced November Room (Fragment from Self-portrait as a Building, reduced to 88%), Greene Naftali Gallery, New York, September 16 - October 14, 2000
Engels
boek
Keywords: Manders, Mark